Living well with inflammatory bowel disease: a UK qualitative survey. (2nd April 2023) - Radford, Shellie J; Sawyer, Rachel
Abstract : Background: Chronic diseases, like inflammatory bowel disease (IBD), pose a significant health challenge in the UK. Addressing the needs of chronically ill patients is one of the important tasks for healthcare systems. To provide optimal support to patients with IBD, it is crucial to gain insight into their priorities. This requires a comprehensive understanding of what matters most to them. By identifying their needs and concerns, we can develop effective strategies to improve their care. Aim: This survey aimed to investigate opinions and personal experiences in relation to what people think are the most important factors when living with IBD and what it means to live well with the condition. Methods: People of any age or gender living with IBD were invited via social media (Twitter) to complete an anonymous online survey, created using Microsoft Forms and comprising three free-text questions to gather in-depth data. Results: From 45 responses, 42 reported symptom burden to be the most impactful aspect of living with IBD, impacting on work, education, social and leisure activities, as well as sex and intimacy. While 26 participants reported that living well with IBD meant to achieve complete symptom resolution, more participants spoke about having manageable symptoms without fluctuation. Achieving a normal level of daily activity was also important to participants. Conclusions: Most participants considered the most impactful aspect of IBD to be symptom management, alongside daily tasks such as work, education, social and leisure activities. They also felt that living well with IBD meant resolving or improving management of symptoms. Further exploration of the magnitude of symptom resolution that would be acceptable or preferable for people living with IBD is warranted.